1980
DOI: 10.1159/000122995
|View full text |Cite
|
Sign up to set email alerts
|

An Inability of Subcutaneous Vasopressin to Affect Passive Avoidance Behavior

Abstract: The effects of subcutaneous injections of vasopressin on the passive avoidance behavior of rats were investigated in an extensive study. 200 male Wistar rats were tested in a step-through passive avoidance task. The animals were assigned randomly to 1 of 20 experimental groups consisting of five vasopressin injection and four shock level conditions. Each animal was trained to enter a dark compartment, then subjected to 0.25, 0.10, 0.05 mA or no foot shock for 2 sec. 60 min prior to a retention test administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Subsequent studies have focused mainly on the effects of exogenous AVP (3)(4)(5), in particular on the interaction between AVP treatment and aversive stimulation (6)(7)(8). Those investigations using specific antisera or antagonists suggested that the endogenous neuropeptide is involved (9-1 1), but direct demonstration of increased intracerebral release of AVP and improved behavioral performance is still lacking.…”
mentioning
confidence: 99%
“…Subsequent studies have focused mainly on the effects of exogenous AVP (3)(4)(5), in particular on the interaction between AVP treatment and aversive stimulation (6)(7)(8). Those investigations using specific antisera or antagonists suggested that the endogenous neuropeptide is involved (9-1 1), but direct demonstration of increased intracerebral release of AVP and improved behavioral performance is still lacking.…”
mentioning
confidence: 99%
“…extinction had been prolonged after periph eral or central administration of vasopressin. However, several recent experiments [Carey and Miller, 1982;Bai-ley and Weiss, 1979;Hostetler et al, 1980;Sahgal et al, 1982] do not confirm the observations from the preced ing studies.…”
Section: Introductionmentioning
confidence: 89%
“…Hostetter et al . found no effect of vasopressin in a food reward task but did find an effect on fear‐motivated behavior; they subsequently reported the inability to reproduce de Wied's findings on passive avoidance behavior . In 1983, Ettenberg et al .…”
Section: The Critical Assaultmentioning
confidence: 96%